Hand adjusting a Beckman Model 746 Solution Metering Pump - Otto, Glenn (1961)
The Model 746 Solution Metering Pump was a product of Beckman's Scientific and Process Instruments Division and incorporated a Helipot Division Duodial. It controlled the flow of liquid to one-millionth of a quart and was used for applications in food processing plants and chemical research laboratories.
Keywords: Pumping machinery; Scientific apparatus and instruments; Beckman Instruments, Inc.